Rapid Shallow Breathing Index Measurement, Modifications, and Predictive Performance for Ventilator Weaning in Adult ICU Patients: A Scoping Review - Sopyan, Tatang; Priambodo , Ayu Prawesti; Nuraeni, Aan (Chakra Brahmanda Lentera Institute, 2026)
Background: The Rapid Shallow Breathing Index (RSBI) is widely used to assess readiness for ventilator weaning in mechanically ventilated patients. However, variations in measurement methods, cut-off values, modifications, and predictive performance have resulted in heterogeneous evidence. This scoping review aimed to map the available evidence on RSBI measurement methods, modifications, and predictive performance for ventilator weaning outcomes in adult ICU patients. Methods: This scoping review followed the Arksey and O'Malley framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guidelines. The Population–Concept–Context (PCC) framework guided the research question. Literature searches were conducted in PubMed, ScienceDirect, ProQuest, SAGE Journals, and EBSCOhost for English-language primary studies published between 2015 and 2026. Data were extracted using a structured charting process and analyzed through thematic synthesis. Results: Of the 461 identified records, 18 primary studies met the inclusion criteria. Four main themes were identified: conventional RSBI performance, variability in measurement methods and cut-off values, serial RSBI monitoring during spontaneous breathing trials, and diaphragm ultrasound-based RSBI modifications. Conventional RSBI showed variable predictive performance across studies because of differences in patient characteristics, ventilator settings, SBT protocols, measurement techniques, and outcome definitions. Conclusion: RSBI remains a simple and non-invasive bedside parameter for ventilator weaning assessment; however, conventional RSBI should not be used as a stand-alone predictor. Its interpretation should be integrated with comprehensive clinical assessment and patient characteristics. Future multicenter studies are needed to standardize RSBI measurement protocols and validate diaphragm ultrasound-based RSBI modifications across diverse ICU populations.